ANALISIS SISTEM INFORMASI PENJUALAN BARANG KOPERASI BERBASIS WEB SEBAGAI PENDUKUNG PROGRAM PELAYANAN PRIMA - Dwi Retnosari; Auliya Rahman (Universitas Lambung Mangkurat, 2020)
The cooperative at Abdul Kadir Panyipatan High School is engaged in trading, which in cooperative sales procedures still has weaknesses in terms of data management and reporting of goods and transaction systems. Students who want to buy a lot of their needs in shopping have to wait a long time in the place of the cooperative, this is because the sales transaction system is still done conventionally and the financial reporting process still refers to the financial ledger. The problem solving method used is the need for procedures and web-based sales information systems using PHP programming and Mysql databases, so that data and reports can be well integrated. The result can be managing data and reports which to archive data supported by web-based information systems can support cooperative employee performance in excellent service so that it helps and facilitates the financial recapitulation process at the end of the year, so sales will be as expected.